Harmonia axyridis in fruit trees and impact on other predator coccinellids - Milléo, Julianne; de Souza, Jana Magaly Tesserolli d; Barbola, Ivana de Freitas; Husch, Patrícia Elizabeth (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the population fluctuation of Harmonia axyridis in fruit trees, during two years (2004–2006), to relate it with abiotic variables and to assess its influence on the other predator coccinellids, in Ponta Grossa, PR, Brazil. H. axyridis represented 38% in Coccinellidae. There was significant difference in the relative frequency of the species between the sampling years, which changed from 0.20 to 0.67, from one year to the other. There was positive significative correlation betweenH. axyridis abundanceand mean temperature, in citric plants, and negative significative correlation betweenH. axyridis abundance and air relative humidity, in noncitric plants. H. axyridis causes negative impact on local ladybugs.